Synthesis of carbon dots by acid dehydration of carbohydrate and activated charcoal / Amilia Amir - Amir, Amilia (2013)
Recently, carbon dots has gained numerous attention due to their remarkable fluorescence properties, potential in bioimaging, high stability over time, non photobleaching and low toxicity. This project is focused on the use of sago starch and activated charcoal to synthesize carbon dots. The resultant carbon dots were analyzed using different spectroscopic techniques such as UV-visible spectroscopy and fluorescence spectroscopy. Our experimental results showed that, carbon dots synthesized from sago gave a successfully produced fluorescent emission at the 478 nm with optimum excitation wavelength of 380 nm. On the other hand, carbon dots synthesized from activated charcoal gave a fluorescence emission at 425 nm upon excitation at 310 nm. The samples when tested under UV lamp at wavelength of 254 nm emit light green fluorescence.